2020
DOI: 10.1093/humupd/dmz045
|View full text |Cite
|
Sign up to set email alerts
|

Disturbed genomic imprinting and its relevance for human reproduction: causes and clinical consequences

Abstract: BACKGROUND Human reproductive issues affecting fetal and maternal health are caused by numerous exogenous and endogenous factors, of which the latter undoubtedly include genetic changes. Pathogenic variants in either maternal or offspring DNA are associated with effects on the offspring including clinical disorders and nonviable outcomes. Conversely, both fetal and maternal factors can affect maternal health during pregnancy. Recently, it has become evident that mammalian reproduction is infl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
82
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 112 publications
1
82
0
Order By: Relevance
“…Recently, a number of maternal-effect variants mostly affecting the components of the oocyte SCMC have been associated with MLID. However, the presence of heterogeneous phenotypes in the offspring of the carrier mothers makes prediction of the clinical condition and determination of recurrence risks very challenging [ 7 ]. Several studies have indicated PADI6 variants as the cause of female infertility [ 16 19 ], but its role in imprinting disorders is less well established [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Recently, a number of maternal-effect variants mostly affecting the components of the oocyte SCMC have been associated with MLID. However, the presence of heterogeneous phenotypes in the offspring of the carrier mothers makes prediction of the clinical condition and determination of recurrence risks very challenging [ 7 ]. Several studies have indicated PADI6 variants as the cause of female infertility [ 16 19 ], but its role in imprinting disorders is less well established [ 20 ].…”
Section: Discussionmentioning
confidence: 99%
“…Most of the maternal-effect genes associated with MLID or hydatidiform mole encode for components of the subcortical maternal complex (SCMC) that is localized in the periphery of the oocyte cytoplasm and early embryo until the blastocyst stage [9]. Among these genes, more compelling pieces of evidence have been provided for association of NLRP2, NLRP5, NLRP7, and KHDC3L, while the role of PADI6, OOEP, and TLE6 in the etiology of imprinting disorders is not definitely established [7]. Although several important functions have been attributed to the SCMC during oocyte-to-embryo transition and early development (for a review, see [9]), the mechanisms through which this protein complex influences methylation imprinting remain elusive.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Genomic imprinting occurs via an epigenetic mechanism, which means that some imprinted genes are only expressed from their maternal allele, while others are only expressed from their paternal allele. Approximately 1% of human genes are normally expressed from only the maternally or paternally inherited gene copy [129]. Mammals are biparental diploid organisms, and both maternal and paternal genomes are required for normal development.…”
Section: Challenges Of Dsc Scnt and Ipscsmentioning
confidence: 99%